KUANTIFIKASI BAU DAN POLUSI BAU DI INDONESIA - Arief Sabdo Yuwono (Department of Environmental Engineering-Faculty of Civil, Environmental and Geo Engineering. Institut Teknologi Sepuluh Nopember, Surabaya, 2008)
Odour is concerned as one of the important environmental nuisance forms in Indonesia. Its presence can be detected by means of human olfactory systems. The term of “odour” contains at least two meanings, i.e. firstly as “sense” and secondly refers to a kind of odorous chemical compound. Principally, odour can be quantified in a number of methods such as odorous gas concentration measurement, by olfactometer, by hedonism scale, as well as by indirect measurement using frequency change of a chemical sensor. Odour quantification is useful to solve the polemics on odour pollution in Indonesia. A number of odour pollution cases are originated from industrial and agricultural activities, such as municipal solid waste treatment, crumb rubber production, intensive animal husbandry, wastewater treatment plant and oil refinery. Odour quantification is a tool to solve odour pollution polemics comprehensively by involving certified independent assessor.